Hey Arnold! the movie [videorecording (DVD)] - Bartlett, Craig; Hecht, Albie; Viksten, Steve, 1960-; Tucker, Tuck; Klein, Spencer, 1986-; Smith, Francesca, 1985-; Smith, Jamil Walker, 1982-; Castellaneta, Dan; MacNeile, Tress, 1951-; Sorvino, Paul; Lee, Jennifer Jason, 1962-; Lloyd, Christopher, 1938-; et al. (Paramount DVD collection., 2002)
When an evil business developer threatens to tear down the neighboorhood to build a shopping mall, Arnold - together with Helga, his annoying secret admirer, and Gerald, his best friend - comes to the rescue.